Unlocking the potential of the geography laboratory as a 21st-century skill-learning hub - Dicky Arinta; Betty Masruroh; Ifan Deffinika; Mohamad Arif; Ramadhani Lausi Mkumbachi; Ahmed Djoumoi (Universitas Negeri Malang, 2024)
Acquisition of 21st-century skills can be achieved through the use of supporting facilities and infrastructure. In the study of geography, the laboratory functions as a learning tool that significantly improves teaching and learning activities. This research identifies and describes the potential for geography-based laboratory learning for management priorities and future development design. For this reason, this research uses mixed methods and descriptive analysis. Held in the Geography Department, Faculty of Social Sciences, State University of Malang. The population in this study consisted of Geography Department students and laboratory managers, while the sample was selected purposively from the class of 2019, totalling 84 students. Primary data was collected through structured interviews with students and in-depth interviews with geography laboratory managers to determine the potential for laboratory development over the last 5 years. Furthermore, this research has secondary data, namely laboratory equipment inventory data. Data analysis was carried out through SWOT analysis. The analysis results show that the geography laboratory consisting of Soil Geography, Geology, Cartography, Geographic Information Systems, Population Geography laboratories has quite large development potential. Conditions in each laboratory require development strategies. The development strategy includes: 1) planning, 2) procurement, 3) inventory, 4) storage, 5) arrangement, 6) utilization, 7) maintenance, and 8) disposal.